Description Of Packaged Food Consumption Behavior Of Nusa Cendana University Public Health Students, Class Of 2020 - Tiran, Marvel; Laga Nur, Marselinus; Liufeto, Mega (Pergizi Pangan DPD NTT, 2026)
Background: High-sugar diets contribute to prolonged increases in blood sugar, insulin resistance, and leptin resistance, all linked to weight gain and excess body fat. The World Health Organization reports that more than 124 million children and adolescents (6% of girls and 8% of boys) were obese in 2016, and half of them lived in Asia. There has been an increasing trend in the proportion of obesity in adults in Indonesia since 2007, which is as follows: 10.5% (Riskesdas, 2007), 14.8%, and 21.8% (Riskesdas, 2013 and 2018). Objectives: This study aims to describe the consumption behavior of packaged food among public health students in Nusa Cendana University's 2020 class. Methods: The type of research used in this study is descriptive research, using qualitative descriptive methods to determine the description of the variables studied. The sample size in this study was 67 students selected by purposive sampling technique. Results: Based on the results of in-depth interviews as well as the results of surveys and observations, researchers found that excessive consumption of packaged food. Conclusions: Students' lack of knowledge of packaged food which is reflected in the habit of reading labels and understanding of poorly packaged food labels so that students are wary of limiting consumption of packaged food.